Análise e Otimização de Projetos de Linhas Aéreas AT e MAT - Tiago Rafael Martins Mendes (2020)
The execution of this dissertation project took place during the graduate traineeship at PROEF where there was a necessity to develop a tool that could easily calculate the sag and tension of the conductor in a very high voltage overhead power line. To develop this tool, firstly were explored the elements that constitute a power line, particularly in very high voltage cases. Then, it was analysed the theory behind the mechanical solicitation to the power line tower, and especially regarding conductor sagging. The method used to develop the calculating tool is explored in the next chapter, explaining how the inserted information is processed to return the desired data. To validate the values obtained in the developed tool, a comparison is made between the data returned by the tool and data from previous lines that were constructed by PROEF. This analysis showed that the obtained values were valid and satisfactory to be used. To complement the developed dissertation and explain how the obtained data is used in the field, the method to sagging and regulation of the conductor was explored based on REN's regulation.